THE DETERMINANTS OF REPRODUCTIVE HEALTH CARE BEHAVIOR IN ADOLESCENT: A CROSS-SECTIONAL STUDY: Determinan Perilaku Pemeliharaan Kesehatan Reproduksi Pada Remaja; Cross Sectional Study - Manurung, Imelda Februati Ester; Takaeb, Afrona E. Lelan; Cruz, Jermias da (Jurnal Berkala Epidemiologi, 2024)
Background: The quality of reproductive health during adolescence determines the quality of reproductive health in adulthood. The 2018 National Socioeconomic Survey found that 11% of adolescents were married before the age of 18, and 0.56% were married before the age of 15. Adolescent reproductive health issues continue to increase every year. Purpose: The study aims to analyze the determinants of reproductive health care (RHC) behavior in adolescents. Methods: This study is an analytic observational research using a cross-sectional design. The research was conducted at SMPN 20 Kupang City in 2022. The sample size are 82 students selected using a random sampling technique. The research variables are the characteristics of respondents, health literacy, parental support, teacher support, perceived vulnerability, seriousness, benefits, barriers, cue to act and RHC behavior. Bivariate data analysis used chi-square, and multivariate data analysis used logistic binary regression. Results: The results show that 57% of the respondents have a deficient reproductive health care behavior. The most dominant variable influencing RHC behavior was living with parents (PR= 4.86; CI= 1.22-19.27). Adolescents who live with their parents are 4.86 times more likely to do RHC compared to adolescents who do not live with their parents. Conclusion: These findings recommend the importance of optimizing the role of parents as peers in providing RHC education for adolescents. Parents who do not live with their children have to pay attention and remind their children to keep doing RHC.